2017
DOI: 10.1186/s12957-017-1184-6
|View full text |Cite
|
Sign up to set email alerts
|

Better survival after breast-conserving therapy compared to mastectomy when axillary node status is positive in early-stage breast cancer: a registry-based follow-up study of 6387 Norwegian women participating in screening, primarily operated between 1998 and 2009

Abstract: BackgroundRecent registry studies on early-stage breast cancer have shown better survival rates when women underwent breast-conserving therapy (BCT) compared with mastectomy (MTX). The aim of this study is to investigate women participating in screening, in all four stages of early breast cancer (T1N0M0, T2N0M0, T1N1M0, and T2N1M0), as to whether there is a survival benefit when women undergo BCT compared to MTX.MethodA cohort of 6387 women aged 50–69, with primary-operated breast cancer from January 1998 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The detailed outcomes of OS, LRR, or distant metastasis (DM) are still unclear in patients with breast cancer receiving PST and BCS with or without WBRT. Thus far, observations in patients with breast cancer receiving PST and BCS followed by WBRT are consistent with those of earlier studies that included patients who did not receive PST but received BCS followed by WBRT [ [1] , [2] , [3] , [15] , [16] , [17] , [18] ]. The necessity of WBRT in patients with breast cancer receiving PST and BCS has never been investigated.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…The detailed outcomes of OS, LRR, or distant metastasis (DM) are still unclear in patients with breast cancer receiving PST and BCS with or without WBRT. Thus far, observations in patients with breast cancer receiving PST and BCS followed by WBRT are consistent with those of earlier studies that included patients who did not receive PST but received BCS followed by WBRT [ [1] , [2] , [3] , [15] , [16] , [17] , [18] ]. The necessity of WBRT in patients with breast cancer receiving PST and BCS has never been investigated.…”
Section: Introductionsupporting
confidence: 88%
“…No study, however, has estimated the requirement of WBRT for patients with invasive ductal carcinoma of the breast (breast IDC) receiving PST and BCS. All evidence of BCS followed by WBRT is based on observations in patients with breast cancer not receiving PST [ [1] , [2] , [3] , [15] , [16] , [17] , [18] ]. The detailed outcomes of OS, LRR, or distant metastasis (DM) are still unclear in patients with breast cancer receiving PST and BCS with or without WBRT.…”
Section: Introductionmentioning
confidence: 99%
“…TM may provide women with a safe alternative to mastectomy or offer improved cosmetic and quality‐of‐life outcomes compared with standard BCS, but high‐quality evidence to support the safety and effectiveness of the technique is lacking. RCTs comparing TM with other techniques are largely inappropriate due to patient and surgeon preference, as well as mounting evidence suggesting long‐term survival benefits for patients undergoing BCS and radiotherapy compared with mastectomy. This large prospective multicentre cohort study assessed current practice and short‐term outcomes of the technique and provided ‘real world’ data from 50 centres regarding complications, rates and management of incomplete excision, and impact of TM procedures on the delivery of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized controlled trials conducted to evaluate the outcomes of BCS compared to mastectomy have found no differences in the disease-free survival and overall survival of patients [2][3][4][5][6][7]. In fact, observational real-world studies using data obtained from national cancer registries have determined that better cancer-specific survival and overall survival outcomes were attained in patients who underwent BCS compared to mastectomy [2,[11][12][13][14]. However, in Thailand, while there has been a rise in the incidence of breast cancer, preference for BCS remains very low.…”
Section: Discussionmentioning
confidence: 99%